Ecthyma gangrenosum aggravated by systemic antibiotics: A case report and literature review - Bibush Amatya; Rishabh Dev Tripathee; Rashmi Sharma; Leison Maharjan (Our Dermatology Online, 2018)
Ecthyma gangrenosum is a cutaneous manifestation of systemic infection caused predominantly by Pseudomonas aeruginosa. We report a case of ecthyma gangrenosum in a child caused by P. aeruginosa who had been previously unsuccessfully treated with systemic antibiotics. A four years old boy presented with the complaints of fever and ulcers on the trunk and extremities. He had been initiated on systemic antibiotics without sending or awaiting reports of blood and skin swab culture and sensitivity. The swab samples taken from the ulcers revealed growth of P. aeruginosa. He was then started on antipseudomonal intravenous antibiotics which eventually led to full recovery. Injudicious use of systemic antibiotics can lead to colonization and infection by opportunistic organisms such as P. aeruginosa. The use of antibiotics has to be based on reports of culture and sensitivity.